SWOT Analysis of the Development of the Market of Freight Services in Samarkand Region and its Priorities - Ishonkulova F. A (Researchparks Publishing, 2021)
The author scientifically and theoretically substantiates the situation and problems of diversification of the freight services market, its services market structure, SWOT analysis of the development of the freight transport services market in Samarkand region and research opportunities for the development of the regional freight transport cluster.